Developments and Applications of Carbon Nanotube Reinforced Cement-Based Composites as Functional Building Materials - Cui, Kai; Chang, Jun; Feo, Luciano; Chow, Cheuk Lun; Lau, Denvid (Frontiers in Materials, 2022)
Carbon nanotube (CNT) is a promising nanomaterial with excellent mechanical, electrical, thermal properties and chemical stability. It has received extensive attention due to its unique multifunctional properties in engineering materials. Researchers have explored the preparation and characterization of CNT reinforced cement-based materials. Studies have shown that adding CNT will significantly improve the performance of cement-based materials. This article introduces the techniques for the dispersion characterization of CNT and summarizes the advantages and disadvantages of these techniques. The functionalized applications of CNT in cement-based materials are then reviewed, including sensing performance, structural health monitoring of concrete, electromagnetic shielding, and other applications. In addition, the application and development prospects of CNT in 3D printing concrete are prospected. Finally, we discuss the existing problems and challenges in developing and applying CNT in cement-based composites and suggested future research.